Combined effects of Crinum glaucum and Allium sativum on performance, carcass traits, and physiological health markers in broiler chickens - Godfrey Odeh Gabriel; Prosper Chukwudi; Adeleke Azeez Odumboni; Tolulope Emmanuel Oluwole; Shina James Owolabi; Timothy Philip Chorio; Mercy Chisara Ogwuegbu (Discover Applied Sciences)
Abstract This study investigated the combined effects of Crinum glaucum and Allium sativum on the growth performance, carcass traits, haematology, serum biochemistry, humoral immunity, and oxidative status in broiler chickens. A total of 256 one-day-old Arbor acres broiler chicks were divided into four experimental treatment groups with four replicates of 16 birds each for a 49-day study. The control group received a basal diet (BD) with 0 g/kg of Crinum glaucum + 0 g/kg of Allium sativum (0CG + 0AS), while the other treatment groups received BD + 1 g/kg of Crinum glaucum + 1 g/kg of Allium sativum (1CG + 1AS); BD + 2 g/kg of Crinum glaucum + 2 g/kg of Allium sativum (2CG + 2AS); and BD + 3 g/kg of Crinum glaucum + 3 g/kg of Allium sativum (3CG + 3AS), respectively. The results revealed a significant linear increase in body weight and body weight gain, alongside improved feed conversion ratio in the treatment groups supplemented with Crinum glaucum and Allium sativum. No significant effect was observed in feed intake. The results showed improvements (p < 0.05) in carcass percentage and in breast, drumstick, and thigh weights. Haematological parameters were not affected, except for packed cell volume and haemoglobin. Significant effects (p < 0.05) were observed for all the serum biochemical parameters except for total protein, globulin, low-density lipoprotein, and total CO2. Furthermore, IgA and IgY levels showed a significant positive quadratic (p = 0.001) and linear effect (p < 0.001), whereas no significant effect on IgM levels was detected. Oxidative status improved significantly, with increased superoxide dismutase, glutathione peroxidase, catalase, vitamin C, and vitamin E, while decreasing malondialdehyde levels. In conclusion, our findings suggest that the combined dietary supplementation with 3 g/kg of Crinum glaucum and 3 g/kg of Allium sativum can enhance the health status and performance of broiler chickens without adverse effects.